Validated Ultra Performance Liquid Chromatography-Tandem Mass Spectrometric Method for Determination of Betamethasone or Dexamethasone in Pharmaceuticals - Amer Shammout, Mohammad J.; Basci, Nursabah Elif (Current Pharmaceutical Analysis, 2018)
Introduction: Chromatographic methods for determination of betamethasone or dexamethasone in their pharmaceutical preparations by Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry were developed. Method: Analytes were eluted from Acquity BEH C18 (50 mm.1 mm, 1.7 μm) column using stepwise gradient with mobile phase consisted of acetonitrile and 0.1% (v/v) acetic acid in water. Quantitation of dexamethasone and betamethasone was performed using 451>361 m/z on MRM mode. Results: Methods were linear over the concentration range from 10 to 1500 ng mL-1 for both analyte. Limits of detection for BTM or DXM were 1 ng mL-1. The highest relative error and relative standard deviation values were not over 2%. Conclusion: Presented methods were specific, rugged and robust, successfully applied to the analysis of their pharmaceutical preparations.
Keywords: betamethasone